Temperature Dependence of the Microstructure and Mechanical Properties of a Twinning-Induced Plasticity Steel - Monsalve-Gonzalez, A; Artigas-Abuin, A; Castro-Cerda, F (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
The objective of the present study is to analyze the microstructure and mechanical properties of a twinning-induced plasticity (TWIP) steel at different temperatures. For this purpose, tensile tests were performed on a Fe-22Mn-0.65C TWIP steel in a temperature range between 25 °C and 400 °C. The microstructure after deformation was characterized via optical microscopy. It was observed that the microstructure consists of mainly deformation twins at low temperatures, whereas dislocation bands are the predominating feature at high temperatures. The analysis of mechanical data suggests a transition of the deformation mechanism from twinning at low temperatures to dislocation slip at high temperatures. The work-hardening rate and area reduction variation with temperature are discussed and correlated to the decrease of twinning contribution to the deformation mechanism. The role of other processes, such as dynamic strain aging and precipitation hardening, are discussed. A thermodynamic-based description for the dependence of yield stress with temperature was developed, suggesting two acting work-hardening mechanisms. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.